1999
DOI: 10.1128/jcm.37.6.2125-2125.1999
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of Vibrio cholerae

Abstract: In our article, we suggested that non-O1 strains of identical or closely similar electrophoretic type (ET) collected on different continents represent clonal lineages (Tables 3 and 5 in the original article). Reconsideration of our data, however, indicates that for many of these sets of strains an equally plausible if not more likely explanation of multilocus genotypic similarity is the independent recombinational assembly of common alleles. This is the case for ET 196 and ET 128 (Table 3), each of which has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…Since our examination of the host range of CP-T1 transduction of CTX⌽ revealed that only 2 of 20 different V. cholerae serogroups, i.e., O1 and O37, were transduced, CP-T1 may not be important in the transfer of ctxAB to most non-O1 strains. Interestingly, the O37 strain has been shown to be closely related to epidemic O1 V. cholerae strains and was associated with a serious cholera outbreak in Sudan in 1968 (2,5,49). Although the CP-T1 host range appears to be limited to a subset of V. cholerae serogroups, it has been proposed that non-O1 serogroups may convert to the O1 serogroup and vice versa under certain environmental conditions, which may allow for the extension of the CP-T1 V. cholerae host range (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Since our examination of the host range of CP-T1 transduction of CTX⌽ revealed that only 2 of 20 different V. cholerae serogroups, i.e., O1 and O37, were transduced, CP-T1 may not be important in the transfer of ctxAB to most non-O1 strains. Interestingly, the O37 strain has been shown to be closely related to epidemic O1 V. cholerae strains and was associated with a serious cholera outbreak in Sudan in 1968 (2,5,49). Although the CP-T1 host range appears to be limited to a subset of V. cholerae serogroups, it has been proposed that non-O1 serogroups may convert to the O1 serogroup and vice versa under certain environmental conditions, which may allow for the extension of the CP-T1 V. cholerae host range (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the serogroups in V. cholerae do not necessarily follow the evolution of its chromosomal backbone, as reflected in phylogenetic trees constructed in other studies (Beltran et al, 1999). For housekeeping genes such as those used for MLST, all of the genes are very closely related, indicating that the vast majority of housekeeping genes have a single lineage or phylogenetic branch for V. cholerae (Beltran et al, 1999;Stine et al, 2000;Garg et al, 2003). In contrast, gmd, a gene for O-antigen biogenesis in V. cholerae O139, has an allele that has greater similarity to E. coli than to Vibrio, consistent with lateral gene transfer (Garg et al, 2003).…”
Section: Phylogenymentioning
confidence: 91%
“…The polysaccharide biogenesis region is one of the most variable regions in the genome and lateral gene transfer has played an important role in its evolution. As a result, the serogroups in V. cholerae do not necessarily follow the evolution of its chromosomal backbone, as reflected in phylogenetic trees constructed in other studies (Beltran et al, 1999). For housekeeping genes such as those used for MLST, all of the genes are very closely related, indicating that the vast majority of housekeeping genes have a single lineage or phylogenetic branch for V. cholerae (Beltran et al, 1999;Stine et al, 2000;Garg et al, 2003).…”
Section: Phylogenymentioning
confidence: 94%
“…It is isolated from muds and waters and also from molluscs and crustaceans (Nair et al, 1988(Nair et al, , 1991. The environmental isolates are much more variable than those of the sixth and seventh pandemics (Beltran et al, 1999;Farfan et al, 2000), which can now be seen to be closely related clones with human pathogenic properties. The VPI was initially thought to be present only in the epidemic V. cholerae isolates, but a number of studies have shown that it is also present in some environmental isolates, with recovery of novel tcpA alleles (Novais et al, 1999;Nandi et al, 2000;Mukhopadhyay et al, 2001;Boyd & Waldor, 2002;Li et al, 2002Li et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%